Rural Investment Climate in Indonesia - McCulloch, Neil (ISEAS Publishing, 2009)
It is a delight to see it published and available to a wide audience." - C. Peter Timmer, Visiting Professor, Program on Food Security and Environment, Stanford University; Non-Resident Fellow, Center for Global Development